Cartografia e poder: o atlas do Império do Brazil e a projeção intelectualizada do território nacional por Cândido Mendes de Almeida (1868 – 1889) - Máximo, Maria Leopoldina Dantas (2023)
ABSTRACT In September 1868, Candido Mendes de Almeida published what would be considered the first Atlas do Imperio do Brazil. The work, intended for the D. Pedro II College, presented a compilation of maps of the territory that formed the Brazilian State and a historical text that was concerned with describing the national and provincial borders from its occupation process, forming part of the most broad scope of construction of the Brazilian nation. The second half of the 19th century marked a process of relative political stability, allowing state agents and the elite to direct various efforts towards the production of 'knowledge about space', which until then was not fully known or mapped, allowing the use of cartography as an instrument of power. Based on these discussions, an analysis was carried out around the debate about how maps, plans and letters, clarified to a historical discourse, were used in the production of narratives that sought to define the borders of a Brazil, paradoxically represented as 'natural'. The research analyzes how this territory, naturalized in these narratives, was built and defined throughout the 19th century, based on disputes and interests of those involved in its representations. Still examining how the construction of the territory sought to help in the idealization of a common identity for the brazilian people, which was imagined.